(untitled) - Soe, Theingi Nan (Can Tho, 2020)
The present study was conducted to determine the effects of temperature and salinity on the maturation and spawning of mud crabs (Scylla paramamosain). The broodstock female mud crabs with an average weight of 200-400g/ind. were obtained from Cà Mau province and eyestalk ablation was done. Mud crabs were reared 60 days at four different temperatures (27-28℃; 30-31℃; 33-34℃ and 36-37℃) using 500-L tanks and an indoor Recirculating Aquaculture System. For salinity effect, mud crabs were stocked in five different salinities (15‰, 20‰, 25‰, 30‰, and 35‰) for 60 days with a water exchange system. The results showed that mud crabs cannot thrive at a higher temperature. After 14 days of stocking in 36-37℃, all mud crab was dead. Also, the higher temperature 33-34℃, the capacity of mud crab to attach eggs to pleopod hairs of the abdominal sac was ceased. The maturation and spawning timing of mud crab was short at 27-28℃. However, an increasing temperature provides stress to the broodstock which finally elongates the maturation and spawning time.
Keywords: Nuôi cua,Crab culture